1983
DOI: 10.1126/science.6298942
|View full text |Cite
|
Sign up to set email alerts
|

Swine Influenza-Like Viruses in Turkeys: Potential Source of Virus for Humans?

Abstract: Influenza A viruses (subtype H1N1), recently isolated from turkeys in different areas of the United States, were determined to be closely related to strains typically associated with pigs. This conclusion was based on comparisons of H1N1 isolates from pigs, humans, ducks, and turkeys with polyclonal and monoclonal antibodies, RNA-RNA competitive hybridization, and replication studies. One of the H1N1 isolates from turkeys caused influenza in a laboratory technician, who displayed fever, respiratory illness, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 12 publications
1
33
0
1
Order By: Relevance
“…The important new finding is that the RSCU signature of the PB1 gene of the 1918 virus is identical to that of the classical swine and human H1N1 viruses (including clade 1 viruses), and not related to that of any of the contemporary avian viruses, although the overall sequence of the PB1 protein is avian-like. To reconcile these observations at least two interpretations are possible: i) An avian virus entered the swine population a long time ago, adapted to pigs to obtain the new RSCU signature, and was able to shift between domestic birds and pigs since they live in a close neighborhood (Hinshaw et al 1983;Webster et al 1992;Ludwig et al 1994) before it entered the human population around 1918; or, ii) a specific avian virus that differed in RSCU signature from the bulk of the other avian viruses was able to enter the pig population easily, possibly a long time ago, and then disappeared as avian virus. From there it may finally have been introduced to the human population shortly before 1918.…”
Section: Discussionmentioning
confidence: 99%
“…The important new finding is that the RSCU signature of the PB1 gene of the 1918 virus is identical to that of the classical swine and human H1N1 viruses (including clade 1 viruses), and not related to that of any of the contemporary avian viruses, although the overall sequence of the PB1 protein is avian-like. To reconcile these observations at least two interpretations are possible: i) An avian virus entered the swine population a long time ago, adapted to pigs to obtain the new RSCU signature, and was able to shift between domestic birds and pigs since they live in a close neighborhood (Hinshaw et al 1983;Webster et al 1992;Ludwig et al 1994) before it entered the human population around 1918; or, ii) a specific avian virus that differed in RSCU signature from the bulk of the other avian viruses was able to enter the pig population easily, possibly a long time ago, and then disappeared as avian virus. From there it may finally have been introduced to the human population shortly before 1918.…”
Section: Discussionmentioning
confidence: 99%
“…This subtype has been shown to spread from pigs to domestic turkeys and to humans (Hinshaw et al, 1983), emphasizing the ability of H 1N 1 viruses to spread between species. Some of the genetic information in the vast pool of influenza virus genes present in aquatic birds may gain access to humans through pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier analysis with a small panel of monoclonal antibodies to A/N J/11/76 (X-53A) H1N 1 (Hinshaw et al, 1983 showed that although the antibodies reacted with two turkey (ty) isolates which were genetically, antigenically and biologically similar to swine (sw) isolates, they did not react with three duck isolates, including dk/Alberta. This suggests that the number of epitopes shared between avian and mammalian H1N1 viruses is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to examine the level of antigenic variation in swine viruses, we prepared and defined a panel of monoclonal antibodies (MAbs) to the haemagglutinin of recent swine isolates. These MAbs were then used to determine whether there was antigenic variation among swine influenza viruses in enzootic areas, H1N1 viruses of swine origin are transmitted to other species, for example since 1980 they have been responsible for disease problems in the U.S.A. in turkeys (Hinshaw et al, 1983;Ficken et al, 1989) and in humans (Dasco et al, 1984;DeJong et al, 1986;Rota et al, 1989). In 1988 a person in Wisconsin, who was exposed to pigs with an influenza-like illness at a fair, died after infection with an H 1N 1 swine influenza virus (Centers for Disease Control, 1988;Rota et al, 1989).…”
Section: Introductionmentioning
confidence: 99%